Ահմեդ Ջևդեթ Փաշայի զեկուցագիրը Հայկական հարցի վերաբերյալ - Սահակյան, Կարոլինա Մ. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Ахмед Джевдетпаша (1822–1895) был ключевой фигурой реформ Османской империи в XIX веке. Он был интеллектуалом, государственным деятелем и историком, известным своим вкладом в правосудие, управление и образование, а также историографию и политику. С целью пролить свет на отношение Джевдетпаши к армянам в этой статье, мы представляем один из его докладов, написанный высокопоставленным османским чиновником по приказу султана АбдулХамида II (1876–1909), в котором наряду с ситуацией в Османской империи упоминается и Армянский вопрос. Ahmed Cevdet Paşa (1822–1895) was a key figure in the 19th century reforms of the Ottoman Empire. He was an intellectual, statesman and historian known for his contributions to justice, administration and education, historiography and politics. His works reflect his views as a witness and participating statesman on Armenians and the Armenian question. In this article, we present one of the reports written by Cevdet Paşa on the order of Sultan Abdul Hamid II (1876–1909) to shed light on the attitude of a high-ranking Ottoman official towards the Armenians.
Keywords: Նորագույն պատմություն